The Effect of Price and Product Quality on Customer Satisfaction - Putri Nilam Kencana (PINISI Discretion Review, 2018)
One example of a franchise that has increased in a number of outlets is fast-food restaurants or often called fast food. The purpose of this study was to determine the effect of price and product quality on customer satisfaction on Giant Fried Chicken Citra Raya. The research method uses quantitative with a population of 22,577 customers, the determination of the sample using the Slovin formula with an error rate of 10% obtained 100 respondents. Data collection methods using primary data and secondary data. Test the instrument using the validity and reliability test, the prerequisite data test uses the normality test, autocorrelation test, multicollinearity test, and heteroscedasticity test, while the statistical test uses multiple regression equations, correlation coefficient test, coefficient of determination test and significance test. The results show that the price and quality of the product have a positive effect on consumer satisfaction with a regression equation Y = 19.846 + 0.329X1 + 0.312X2 + e. The better the price determination and the higher the quality of the product, the more it will increase customer satisfaction. Vice versa, if the price and quality of products are low, customer satisfaction will also decrease. The simultaneous contribution of price and product quality is 40.8% while the remaining 59.2% is influenced by other factors. the calculated F value is greater than the F table or (9669> 3.090), it is also reinforced by the significance of 0,000 <0.05. Thus H0 is rejected and H1 is accepted. This means that there is a positive and significant effect simultaneously between price and product quality on customer satisfaction on Giant Fried Chicken Citra Raya.